Design and fabricate a go-kart motor fixing holder and gearing system - Mohamed Samud, Nur Adlin Farhana; Mohd Yusof, Ab Aziz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This study focuses on the design and analysis of motor fixing holders and gearing systems for small-scale vehicles, specifically go-karts. The primary objective is to achieve an optimal balance of power output, torque, and speed to enhance both performance and efficiency. The research involves selecting suitable motors, whether gasoline or electric, and integrating gearing systems such as centrifugal clutches and torque converters. Through theoretical analysis and practical experimentation, various gear ratios will be evaluated to assess their effects on acceleration, top speed, and handling. Additionally, the study examines weight distribution in relation to the power-to-weight ratio and its impact on system performance and safety. The findings will provide guidelines for designing efficient and reliable motor fixing holders and gearing systems, contributing to a better understanding of their applications in both recreational and competitive go-karting. Ultimately, this research advances vehicular engineering by offering insights into the interaction between mechanical components and dynamic performance.